Experimental model for the study of ascites in dogs - Goicochea Vargas, José (2009)
The research was carried out at the Hermilio Valdizan University Huanuco - Peru, in order to make uniform the experimental model for the study of ascites in dogs, by reducing the size of the posterior vein cava, using ad hoc rings preparad from rectal probe and flexible silicone to make knowing the changas of plasma proteins and ascitic fluid during the installation of ascites. The study was conducted in 05 apparently healthy animals of different age, sex and weight. In 100% of the animals had ascites to 13.2 days ± 4, 1 and with an increase of the abdominal average perimeter of 63,4 cm with regard to the basal preoperative control of 53 cms. ± 1.2 and not happening any death in the animals. The behavior of plasmatic proteins resultad in an average decrease when they presentad the ascites of 3.30 g I di ± 0.32 with respect to preoperative found values in the 4.89 g I di± 0.35, with the fraction albumin 2.00 g I di± 0.91, which declinad from the basal level of 2.98 g I di ± 0.35 (p s 0.05), globulin increased on average in animals with ascites 1.71 g I di± 0.66 to 1.90 g I di± 0.31, while total protein was 3.30 g I di ± 0.32 in animals with ascites as opposed to 4.89 g I ± 1.20 di, who presentad preoperatively. lt is considerad as a versatile and practica! model for the study of experimental ascites in dogs, it is reduced the mortality, in addition to shortening the time it was obtained when it is comparad with the results of other surgical methods.